Information Quality and Data Quality in Accounting Information System: Implications on the Organization Performance - J.A. Ali , Basel; Salem Oudat, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
In recent periods, the majority of organizations have recognized the significance of Accounting Information Systems (AIS) in their operational or financial activities towards higher performance. As such, this study investigates the relationship between information quality and data quality in AIS and its effects on organizational performance among commercial and Islamic banks in Jordan. The study adopts proportionate stratified random sampling among users of AIS within sixteen commercial and Islamic banks in Jordan. A total of 600 copies of questionnaires were distributed and self-administered, but only 250 copies among the returned questionnaires were valid, suggesting a valid response ratio of 41.1%. In order to estimate the model, this study applies the partial least squares (Smart PLS 3) approach for further hypothesis testing and data analysis. Findings show that information quality is an important factor that enhances organizational performance, while data quality is negative and insignificant. To become and remain competitive, commercial and Islamic banks need to implement a high-quality AIS, as it helps organizations to obtain better performance. Given the negative and significant coefficient of data quality, it implies that information quality is a strategic factor for an organization’s survival. As a way of recommendations, high priority and more emphasis should be placed on the continuous improvement of AIS among the banks, as that will enable them to keep pace with technological developments within the financial sector. The outcome of this approach will also reflect positively on the bank’s administrative functions, particularly in the areas of planning and decision-making.